If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2c+6)=3c-5
We move all terms to the left:
4(2c+6)-(3c-5)=0
We multiply parentheses
8c-(3c-5)+24=0
We get rid of parentheses
8c-3c+5+24=0
We add all the numbers together, and all the variables
5c+29=0
We move all terms containing c to the left, all other terms to the right
5c=-29
c=-29/5
c=-5+4/5
| 5w+w=54 | | (5x+14)/6=4 | | 12=2/3(w-2) | | 1x+18=24 | | 18+1y=15 | | 4+42x=28x=12 | | |9x-7|=-43 | | 5-6u=-13 | | (X+7)(x-9)X=0 | | 5x+14/6=4 | | 6x+11=96 | | n/3-1=6 | | -6+11x=98 | | 5(3-2x)=35 | | -11+20z=-5 | | x+(x-24)+(x+18)=126 | | |9x-7|=43 | | 4/5m-6=18 | | v/3+11=15 | | 12=8+2c | | -6+7/9a=-21 | | 9m^2-2m=8 | | 4b=3(3b+4) | | (a-10)*(a*10)=200a= | | 13x+26=3 | | 3x+26+79=180 | | -1+14x=12x+17= | | 12x+32=7x-6 | | 3(2-a)=15 | | 4x-9=11×-2 | | -2x-6-22x-3=180 | | 9.8t^2+150=0 |